The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/microorganisms9091904
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Analysis of Carious Lesions in Pre-School Children with Early Childhood Caries and Congenital Heart Disease

Abstract: Oral bacteria have been associated with several systemic diseases. Moreover, the abundance of bacteria associated with caries has been found to be higher in patients with congenital heart disease (CHD) than in healthy control groups (HCGs). Therefore, this study aimed to evaluate the dental microbiota in children with CHD compared to a HCG. The aim was to describe and compare the carious microbiome regarding the composition, diversity, and taxonomic patterns in these two groups. Twenty children with CHD and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Olsenella is a genus belonging to the Actinobacteria phylum. Studies have shown that it is highly relevant to dysbiosis and inflammation [ 38 , 39 ]. Ruminococcaceae-UCG -009 has been reported to be pathogenic bacteria when stimulated by stress, leading to an increased intestinal permeability, disrupted epithelial barriers, and intestinal diseases [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Olsenella is a genus belonging to the Actinobacteria phylum. Studies have shown that it is highly relevant to dysbiosis and inflammation [ 38 , 39 ]. Ruminococcaceae-UCG -009 has been reported to be pathogenic bacteria when stimulated by stress, leading to an increased intestinal permeability, disrupted epithelial barriers, and intestinal diseases [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results provide a reference for further exploring the relationship between Olsenella and MetS. Several studies have indicated a significant association between Olsenella and dysbiosis as well as inflammation [59][60][61]. Dysbiosis and inflammation in the gut can compromise the integrity of Fig.…”
Section: Discussionmentioning
confidence: 59%
“…All of them were affected by early childhood caries. The microbiome profile indicated that Fusobacterium, Prevotella, Capnocytophaga, and Oribacterium were more abundant in the CC group, while Lactobacillus and Rothia were predominant in the healthy control [27].…”
Section: Resultsmentioning
confidence: 98%